Enhancing democratic accountability in health and social care: The role of reform and performance information in Health and Wellbeing Boards. (22nd August 2019) - Grubnic, Suzana; Cooper, Stuart
Abstract: The UK government passed the Health and Social Care Act in 2012, and a key element of this legislation was the introduction of Health and Wellbeing Boards (HWBs) in local government. HWBs were argued to have the potential to both improve democratic accountability and give greater autonomy to health and social care leaders to strengthen local health outcomes. This paper explores how members of HWBs construct and discharge accountability for better health outcomes to a local population. We find that there are multiple types of accountability present and that democratic accountability can be complemented by and compete with other types of accountability.